PHYSIOTHERAPY MANAGEMENT IN A 2-MONTH POST-OPERATIVE ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION (ACLR) CASE AT A3 PHYSIO CENTER YOGYAKARTA: A CASE REPORT - Muthia Endang Safitri; Wijianto; Anggi Wahyu Sudianingrum (JTH: Journal of Technology and Health, 2026)
Anterior Cruciate Ligament (ACL) injury can cause pain, limited range of motion, knee instability, and impaired functional activities. ACL reconstruction should be followed by physiotherapy rehabilitation to support the recovery of knee function. This study aimed to describe the examination, physiotherapy management, and intervention outcomes in a patient with post-operative Anterior Cruciate Ligament Reconstruction (ACLR). The study used a case report design on a 20-year-old male patient with a right knee post-operative ACLR condition two months after surgery. The intervention was conducted in three sessions over three weeks at A3 Physio Center Physiotherapy Clinic, Yogyakarta. Evaluation was performed using the Numeric Rating Scale (NRS), goniometer, Manual Muscle Testing (MMT), and International Knee Documentation Committee (IKDC). Physiotherapy interventions included TENS, ultrasound, massage gun, patellar mobilization, functional knee exercises, active resisted exercise using a theraband, education, and a home program. After therapy, movement pain decreased from 5/10 to 0/10, resting pain decreased from 2/10 to 0/10, and pressure pain decreased from 3/10 to 0/10. Active ROM of the right knee increased from S: 0º–0º–125º to S: 0º–0º–127º. Quadriceps and hamstring muscle strength remained at 5/5. The IKDC score increased from 58 to 88. Physiotherapy management in post-operative ACLR patients can reduce pain, increase ROM, maintain muscle strength, and improve knee functional ability.